Effect of different shading levels on Ficus carica physiology - Abdul Wahab, Mohd Nadzeem (2019)
Ficus carica is a deciduous shrub or small tree in the Moraceae (mulberry family) that originated in the Mediterranean, was domesticated over 6,000 years ago as one of the most ancient fruit crops. However, the growth of F. carica in indoors is unknown either the physiological properties of the F. carica shows difference or not. Therefore, this study was carried out in Universiti Putra Malaysia to elucidate the growth of two F. carica variation which is Masui Dauphine and Improved Brown Turkey in two different shading levels which is shaded and not shaded area. Tree growth data is measured by diameter 2cm from tree ground and height in every weeks for about a month and finally the physiological changes of the F. carica in two variation and two shading levels is measured by LICOR 6400. The results shows a difference in between light intensity and the growth of each variations. Hence, F. carica has a potential to grow in indoors.